FOURIER-LAPLACE OPERATOR TRANSFORMATION FOR A CONVOLUTION ALGEBRA OF GEVREY ULTRADISTRIBUTIONS - Лопушанський, Олег Васильович; Соломко, Андрій Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A vector analogue of operator calculus for generators of strongly continuous n -parametric semigroups of operators in the convolution algebra of Gevrey ultradistributions with supports in the positive n -dimensional cone is constructed. The theorem about representation of convolution Gevrey algebra of ultradistributions as commutant of the n-parametric (C0 ) -semigroup of shifts is proved.